The 'Emperor of Persia': 'Empire' as a Means of Describing and Structuring the World. (October 2017) - Mauntel, Christoph
From the late eleventh century onwards, the crusades brought Latin Christianity into direct contact with Muslim powers in the Near East. For the chroniclers of these events, the task of coping with the diversity of different Muslim actors the Christians faced was extremely challenging. Basically, they had two options to describe their respective political order: they could either use the rulers' titles in the version supplied by the original language (i.e., sultan or caliph ) or they could refer to them by using Latin terms (i.e., rex or imperator ). An analysis of the way in which different crusade chroniclers described the political landscape of Islam in the Near East reveals interesting insights: ethnic denominations such as 'Turks' or 'Saracens' alternated with classical terms such as 'Babylonians' and 'Persians' thereby evoking ancient empires that were part of the medieval theory of translatio imperii . The Seljuk Sultan, for example, was frequently presented as the 'emperor of Persia'. Thus, the Muslim states of the eleventh and twelfth centuries were at least to some extent presented as being part of the historical process of evolving and declining empires. The present article asks first how different chroniclers coped with the difficulty of naming and defining foreign political orders and thus developed distinctive interpretations of the history of these empires. Second, the article traces the way in which these models could be adopted by 'non-crusade' historiography: the example of William of Malmesbury shows that the English chronicler used the account by Fulcher of Chartres, but developed a remarkably distinctive version. Underlying his accounts is an overall theory of a continuing presence of eastern empires against the changing nature of politics in Christian Europe.